DESAIN KELOMPOK KERJA UNTUK PENINGKATAN MUTU PENDIDIKAN DI KELOMPOK KERJA RAUDHATUL ATHFAL KABUPATEN PURWAKARTA - Saepul Mukti; Mohammad Fikri Rafsanjani; Rijal Muhamad Kosim; Nizar Muhammad Fasya; Uus Ruswandi (Hijri, 2026)
Improving the quality of early childhood education requires professional and collaborative institutional management, particularly through strengthening the role of Raudhatul Athfal (RA) principals. The Raudhatul Athfal Working Group (Kelompok Kerja Raudhatul Athfal/KKRA) serves as a strategic forum for the professional development of RA principals in enhancing the quality of educational management and services. This study aims to explain the concept and functions of educational working groups, describe the ideal design of working groups for improving educational quality, and analyze the implementation and evaluation of the working group design in the KKRA of Purwakarta Regency. This study employed a qualitative approach with a case study design. The research subjects consisted of KKRA administrators, RA principals, and RA educators selected through purposive sampling. Data were collected through in-depth interviews, observations, and document analysis. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that the KKRA of Purwakarta Regency has a relatively effective working group design, characterized by a participatory organizational structure, democratic leadership, needs-based work programs, and open communication. The implementation of KKRA programs contributes positively to the improvement of RA principals' competencies, the strengthening of institutional management, and innovation in educational governance. However, several challenges remain, including limited funding, time constraints, and varying levels of member participation. This study concludes that a well-planned, collaborative, and sustainable working group design is a key factor in improving the quality of RA education.